PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 42 PEKANBARU - Sere Perawati Samosir; Lazim N Lazim N; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background in this research is the low social achievement of third grade students SDN 42 Pekanbaru. The KKM determined by the school is 73. Out of 36 students, only 14 students (38.88%) reach KKM and 22 students (61.12%) who have not reached KKM with grade 61.47 grade average. This study aims to improve the learning outcomes of social achievement of third grade students SDN 42 Pekanbaru by applying cooperative type model of talking stick. This study presents the learning results obtained from daily test scores before the action with an average of 61.47 increased to 71.66 in cycle I, and increased again to 76.52 in cycle II. Teacher activity in the first cycle of the first meeting gained a percentage of the percentage of 66.66% good category, at the second meeting increased by the percentage of 75.00% with good category. Next cycle II first meeting of teacher activity also increase with percentage of 83,33% good category and at second meeting increase again with percentage equal to 91,67% very good category. While the activity of student in cycle I meeting one get percentage of student activity equal to 62,50% with less, at second meeting increase with percentage 75,00% with good category. Next on the second cycle of the first meeting of student activity increased with the percentage of 83.33% good category and at the second meeting increased with a very good 91.66% category percentage. Based on the results of this study, it can be proved that the appliement of cooperative type talking stick learning model to improve the learning student’s social subject learning result at third grade SDN 42 Pekanbaru.Key Words: Cooperative learning model type talking stick, learning outcomes social